Modification of EBV Associated Lymphomagenesis and Its Immune Control by Co-Infections and Genetics in Humanized Mice - Schuhmachers, Patrick; Münz, Christian (Frontiers in Immunology, 2021)
Epstein Barr virus (EBV) is one of the most successful pathogens in humans with more than 95% of the human adult population persistently infected. EBV infects only humans and threatens these with its potent growth transforming ability that readily allows for immortalization of human B cells in culture. Accordingly, it is also found in around 1-2% of human tumors, primarily lymphomas and epithelial cell carcinomas. Fortunately, however, our immune system has learned to control this most transforming human tumor virus in most EBV carriers, and it requires modification of EBV associated lymphomagenesis and its immune control by either co-infections, such as malaria, Kaposi sarcoma associated herpesvirus (KSHV) and human immunodeficiency virus (HIV), or genetic predispositions for EBV positive tumors to emerge. Some of these can be modelled in humanized mice that, therefore, provide a valuable platform to test curative immunotherapies and prophylactic vaccines against these EBV associated pathologies.